Los reglamentos y normativas de bibliotecas universitarias españolas disponibles en páginas web. - Fernández Falero, Mª del Rosario (Revista General de Información y Documentación, 2001)
The ami of this work has been to locate those Spanish university libraries which present their regulations and/or standards on web pages. A record has been designed to collect and present the basic information which recognises and identifies each regulation. The study is structured as follows: an introduction dealing with methodology and aims; two sections about Spanish universities with regulations on their web site and Spanish university libraries which only Ixave standards for certain subjects on their web site; finally, conclusions aud bibliography.